2018
DOI: 10.1186/s12886-018-0674-9
|View full text |Cite
|
Sign up to set email alerts
|

The necessity and optimal time for performing pars plana vitrectomy in acute retinal necrosis patients

Abstract: BackgroundTo compare the efficacy of pars plana vitrectomy (PPV) at different time points to treat acute retinal necrosis (ARN) and to investigate the necessity of PPV for ARN.MethodsA retrospective review of the treatment options and outcomes of the ARN patients was performed. Thirty ARN patients (34 eyes) were included in this study. The eyes were divided into 3 groups depending on the treatment administered. In the medically treated group, there was no retinal detachment (RD) at the first visit. The routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Whether prophylactic PPV is beneficial in lowering the risk of RD secondary to ARN has remained controversial in current studies. 7,15,16 Our study indicated a positive role of prophylactic PPV, patients who…”
Section: Prophylactic Pars Plana Vitrectomysupporting
confidence: 50%
“…Whether prophylactic PPV is beneficial in lowering the risk of RD secondary to ARN has remained controversial in current studies. 7,15,16 Our study indicated a positive role of prophylactic PPV, patients who…”
Section: Prophylactic Pars Plana Vitrectomysupporting
confidence: 50%
“… 12 A recently published retrospective case series also reported disappointing visual outcomes in patients with ARN despite early pars plana vitrectomy surgery. 13 …”
Section: Discussionmentioning
confidence: 99%
“…15,36 While there are multiple vision-threatening complications of ARN, RRD remains the primary cause of significant vision loss during the clinical course. 12,14,24,37,38 Patients with macula-involving retinitis or an associated optic neuropathy typically do poorly despite successful RRD repair. 7,39 Surgical success in the repair of ARN-associated RRDs can be complicated by the unique features of these detachments.…”
Section: Distinct Features Of Arn-associated Retinal Detachmentsmentioning
confidence: 99%